Reliability-Centered Maintenance to reduce economic losses in the milling area of a sugar company - Martinez Jimenez, Mary Esthefany; Sánchez Pérez, Joselito (LACCEI, 2025)
This research focused on proposing a maintenance management based on RCM to reduce economic losses in the milling area of a sugar company. Likewise, the maintenance process was diagnosed through interviews, documentary analysis and audits, identifying problems such as increased corrective maintenance and poor maintenance management. Considering this, a management proposal based on RCM was developed, using tools such as FMEA and criticality analysis, which resulted in significant improvements in maintenance indicators. Reliability increased from 5,54 hours to 3,22 hours, reflecting an increase of 84,01%, while maintainability decreased by 95,38%, from 2,18 hours to 0,1 hours. In addition, equipment availability increased by 20,75%. These improvements contributed to a 33,61% reduction in economic losses, from S/ 19 768 419,07 to S/ 13 715 776,62. In addition, the economic and financial evaluation demonstrated the viability of the project, with an NPV of S/ 1 726 129,54 and an IRR of 24,71%. Finally, the cost benefit of 1,75 was determined, which is greater than one, that is, the benefit is greater than the investment cost, having a payback period of 5 months, which means that the project is viable for the company.